Practice of Implementation of Health Education in Schools of the Republic of Poland - Larysa Slyvka (Vasyl Stefanyk Precarpathian National University, 2021)
The article substantiates the urgency of the problem of health promotion through education and upbringing. The increased attention of scientists to the problems of the theory and practice of health pedagogy is revealed, the vectors of scientific researches in this sphere are determined. The need to use the positive elements of the experience of foreign countries in the theory and practice of domestic health education is emphasized. The purpose of the article is to highlight the content and some forms of implementation of health-oriented educational programs in the educational process of schools in the Republic of Poland. The research methods were aimed at describing the legislative basis of health care activities in Polish schools; analyzed a number of legislative documents of the Republic of Poland on health of children and youth - "National Health Program" (1990), the Law "On Education" (1991), the Law "On Physical Culture" (1996), the Law "On Reform Education System" (1999), Order of the Minister of National Education "On the Basic Curriculum of Preschool and General Education" (2008). The most important strategies and tactics of this process in this country are highlighted. A variety of methodological approaches have been used to provide the most objective and holistic view of the research problem. The analysis of health-preserving activity of 10 schools of the Republic of Poland is carried out: kindergarten-schools № 7 of Krakow, state primary school named after St. Kinga in Zhegochyn, state primary school № 11 named after Lviv Eagles in Opole, association of schools with integration departments (primary school № 13 and gymnasium № 3) in Myslowice, association of schools № 2 named after John Paul II in the village of Nazzym, Warmian-Masurian Voivodeship, primary school № 10 in Tarnowskie Gory, primary school in Nivka, primary school № 42 named after Stanisław Staszyc in Łód, primary school № 23 named after John Paul II in Rzeszów, primary school № 20 in Katowice. The diversity of health-oriented educational influences has been revealed. The author presents the content and forms of implementation of the following programs in schools: "My child goes to school", "A glass of milk", "Keep fit", the National AIDS Program and HIV prevention, "Clean air around us", "Fruit and vegetables at school", "Healthy eating and physical activity in schools", "Don't fall for me, please". The author offers prospects for further research - a comparison of practical and methodological aspects of solving the problem of health of a growing individual in secondary schools in Poland and Ukraine.